Single and double electron capture by fast Xe54+ from Kr and Xe. (July 2015) - Yu, Deyang; Shao, Caojie; Lu, Rongchun; Wang, Wei; Liu, Junliang; Xue, Yingli; Song, Zhangyong; Zhang, Mingwu; Yang, Bian; Ruan, Fangfang; Cai, Xiaohong
Synopsis: Decay X-ray spectrum of the scattered ions in 52-197 MeV/u Xe 54+ collision with Kr and Xe atoms are measured. The transitions form the single capture ion Xe 53+ * and from the double capture ion Xe 52+ * are observed, both in a single collision. The single capture is the dominate channel at high energies while the double capture becomes dominate at lower energies.